Genomic Education at Scale: The Benefits of Massive Open Online Courses for the Healthcare Workforce - Bishop, Michelle; Miller, Edward; McPherson, Amelia; Simpson, Siobhan; Sutherland, Stuart; Seller, Anneke (Frontiers in Genetics, 2019)
To support the delivery of the UK’s 100,000 Genomes Project, Health Education England’s Genomics Education Programme developed a suite of resources, including a three-week Massive Open Online Course (MOOC) on whole genome sequencing via the FutureLearn platform. This MOOC is a synchronous learning event, with course educators and mentors (NHS healthcare science trainees in genomics) facilitating the experience in real time. Crucially, the platform allows participants to interact and learn from each other’s experiences. The evaluation of the course was considered from the learners’ and mentors’ perspectives. Perceptions of course relevance were examined through analysis of learner comments made throughout the course and responses to an end of course survey. Evaluation of mentors’ experiences focused on how prepared they felt to undertake their role and the value and benefit of their experience. Data was collected through a mixed methods study after the first two runs of the course. Over six iterations, the course had registered over 19,000 learners, including a range of healthcare professionals. The course met learners’ needs by providing a greater understanding of whole genome sequencing and the application of this technology in health care. Learners also highly valued the engagement with mentors. Mentors appreciated the experience and identified areas of professional development gained through the mentoring experience. Our findings show that a team of specialist healthcare course mentors engaging with a range of different healthcare professional MOOC learners in online conversation can enhance the learners’ experiences and provide a beneficial continuing professional development opportunity for mentors.